2012
DOI: 10.1016/j.expneurol.2012.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of estradiol replacement in the olfactory system

Abstract: Olfactory dysfunction often precedes other clinical symptoms in chronic neurodegenerative diseases like Alzheimer’s and Parkinson’s disease. Estrogen deficiency and apoE genotype are known risk factors in these diseases and these factors also affect olfaction. Therefore we examined the effects of estradiol replacement following ovariectomy on expression of apoE and markers of cell proliferation, neuronal maturation, synaptogenesis and reactive gliosis in the primary olfactory pathway of wild-type (WT) and apoE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Many controversial studies have reported altered olfactory sensitivity via central and peripheral effects that correlates with changes in steroid hormone level in females [ 8 , 9 , 43 48 ]. Nevertheless, studies focusing on the direct modulation of neurons in the OE are lacking, and the exact molecular mechanisms modulating olfactory perception are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Many controversial studies have reported altered olfactory sensitivity via central and peripheral effects that correlates with changes in steroid hormone level in females [ 8 , 9 , 43 48 ]. Nevertheless, studies focusing on the direct modulation of neurons in the OE are lacking, and the exact molecular mechanisms modulating olfactory perception are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that estradiol treatment in mice alters the olfactory epithelium [44]. After estradiol treatment, the astrocyte density and the thickness of the olfactory epithelium was increased.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of work shows that peripheral chemosensory signaling can be modified by experience and internal state 2 26 27 28 , as well as by the activity of structures that process multisensory information 29 . The main olfactory epithelium expresses α- and β-type estrogen receptors 30 , and estrogen replacement can protect against olfactory sensory neuron (OSN) loss in gonadectomized mice 31 32 , suggesting that sex and hormone effects could have a peripheral locus. Similarly, the vomeronasal organ undergoes state-dependent filtering in which sex hormones influence the responses of peripheral sensory neurons to specific chemical cues and consequently also behavioral responses to those cues 33 34 .…”
mentioning
confidence: 99%